Laser on erbie glass with diode pumping - Дзюбенко, М.И.; Пелипенко, В.П.; Коленов, И.В.; Дахов, Н.Ф. (Radiotekhnika, 2019)
The results of studies aimed at the development and creation of an erbium-diode-laser laser with diode pumping and providing an output energy of several millijoules in pulses of 20-30 ns duration at a repetition rate of 0.5-1.0 hertz are presented. The interest around this laser is due to the fact that its radiation falls into the spectral region, which is relatively safe for vision. In this spectral region there is a transparency window in the earth’s atmosphere. Thus, half-micron radiance can be used efficiently for location aims and rangefinder. This is facilitated by the presence of highly sensitive uncooled photo detectors. In addition, the spectral region of 1.5-1.6 μm matches with the region of maximum transparency of quartz optical fibers used in fiber-optic communication lines. The experimental sample of ytterbium-erbium laser emitting at a wave length of 1, 54 μm was designed and manufactured. Pumping of active element was done according to the transverse scheme by two laser diode rulers with a power of 100 W each, which has been put in line. The selected pump scheme provides a high excitation power and eliminates the occurrence of a temperature gradient in the active element. To increase the pumping efficiency, a cylindrical active laser element was placed in a sapphire cylinder, the outer surface of which had a reflective coating. During free generation regime, we implemented the optimization of laser characteristics, depending on the Q-factor of resonator and excitation conditions. To obtain a giant impulse, a passive Q-switch based on aluminum-magnesium spinel with cobalt was used in the work. In the Q-switched mode, single pulses with the energy of 6 mJ were obtained with a duration of less than 30 ns at a pulse repetition rate of one hertz.